Pengembangan Potensi dan Daya Tarik Wisata di Kabupaten Bondowoso - Kris Hendrijanto; Purwowibowo Purwowibowo; Budhy Santoso; Syech Hariyono (Journal of Tourism and Creativity, 2021)
Bondowoso is a district in the Besuki Raya area, which is different fromvother areas. This district does not have a marine area, while other Besuki areas, such as Situbondo, Jember, and Banyuwangi districts have coastaland marine areas. Under these conditions, the tourism development program is focused on the potential that exists on the mainland. In order to make Bondowoso Regency a tourist destination that can attract tourists, both domestic and foreign, the Bondowoso Regency government has created a potential and attractiveness development program, through the decision of the Bondowoso Regent, Number 83 of 2016. The Department of Tourism, Youth and Sports to oversee the realization of Bondowoso Regency to become a leading destination, by developing tourism programs based on its local potential. Several tourism destination development programs have been realized by continuing to improve the various infrastructure and facilities needed. This is intended to make it easier for tourists to visit various potential tourist destinations in Bondowoso Regency.